Optimal contract design for carbon emission reduction in a green supply chain: Monetary incentive vs. symbolic incentive - Yangyang Wang; Lan Fang; Mingchun Jiang (Managerial and Decision Economics, 2024)
A supply chain with a manufacturer and a seller is studied in this paper for the impact of monetary and symbolic incentives on reducing carbon emissions. It is the responsibility of the manufacturer to invest in carbon emission abatement technologies and that of the seller to sell such products to consumers with green preferences. The study findings reveal that (1) both monetary and symbolic incentives can contribute to reducing carbon emissions but the choice between them depends on the trade-off between the cost-sharing ratio and the market interest rate; (2) implementing a hybrid policy could crowd-out carbon emission effects; and (3) the manufacturer may maximize his profits under a hybrid policy, but the seller may struggle to cover his expenses, which could hinder effective collaboration within the supply chain.
Keywords: 330